Definition of the jurisprudence rulings of family-based Islamic architecture and urban planning with an emphasis on the Nafye Saabil Jurisprudence As a mandatory rule - Asghar Molaei (پژوهش‌های فقهی مسائل مستحدثه)
The family has an important place in Islamic architecture and urban planning. So that the model of architecture and urban planning based on the family requires compliance with requirements in spatial and physical, functional and management aspects, which lack of attention has led to the construction of residential settlements, towers and apartment complexes, which have many problems and problems such as deprivation It creates comfort and peace for families. The jurisprudential rule of negation of mustache, which is one of the most important and famous jurisprudential rules of Islam, like all other jurisprudential rules, is for the welfare of Muslims. In many verses of the Holy Qur'an, it has been emphasized in denying the rule of infidels over Muslims. Therefore, the purpose of this article is to explain the position of the family in the jurisprudence of Islamic architecture and urban planning, which is done with the research method of text content analysis and logical reasoning with an interdisciplinary study approach and using library and documentation methods. to be The results of the research show that the Islamic city, neighborhood, and house are the places of manifestation and application of jurisprudence rules, including the rule of negation of the mustache, so that according to the rule of negation of the mustache, in the Islamic neighborhood, the ground for the implementation of divine rules, including the centrality of the mosque, should be provided and the model The house is based on a family with a yard and low density and is safe and secure so that the Islamic lifestyle can be realized with the support of Islamic architecture and urban planning.